2019
DOI: 10.1111/tgis.12587
|View full text |Cite
|
Sign up to set email alerts
|

Extending Processing Toolbox for assessing the logical consistency of OpenStreetMap data

Abstract: OpenStreetMap (OSM) produces a huge amount of labeled spatial data, but its quality has always been a deep concern.Numerous quality issues have been discussed in the vast literature, while the fitness of OSM for road navigability is only partly explored. Navigability depends on logical consistency, which focuses on the existence of logical contradictions within a data set. Researchers have discussed the insufficiency of established methods and the lack of a computational paradigm to assess the quality of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 64 publications
(126 reference statements)
1
6
0
Order By: Relevance
“…OSM destination and edge validation comprises a quantitative analysis to compare OSM-derived data against available local official data for evaluating the data quality, representation, and suitability for indicator calculation. In this process, the proportion of overlap between the OSMderived dataset (i.e., edges and destinations) and official dataset within 10-and 50-m buffer are Walkability index (sum of z-scores of population density, intersection density and daily living score) Between city, spatial average … all_cities_z_nh_population_density Local neighborhood population per square kilometer (z-score relative to all cities) all_cities_z_nh_intersection_density Local neighborhood intersections per square kilometer (z-score relative to all cities) all_cities_z_daily_living Daily living score (z-score relative to all cities) all_cities_walkability Walkability index (sum of z-scores relative to all cities) first evaluated, in line with other studies that address road networks' representation with specific thresholds (Sehra et al, 2020). Second, a suitability analysis is conducted to evaluate the accessibility method (i.e., hexagon grid validation), which does not distinguish between hexagon neighborhoods that have one destination or ten destinations: in either scenario, there is access to at least one destination.…”
Section: Osm Destination and Edge Validationsupporting
confidence: 62%
“…OSM destination and edge validation comprises a quantitative analysis to compare OSM-derived data against available local official data for evaluating the data quality, representation, and suitability for indicator calculation. In this process, the proportion of overlap between the OSMderived dataset (i.e., edges and destinations) and official dataset within 10-and 50-m buffer are Walkability index (sum of z-scores of population density, intersection density and daily living score) Between city, spatial average … all_cities_z_nh_population_density Local neighborhood population per square kilometer (z-score relative to all cities) all_cities_z_nh_intersection_density Local neighborhood intersections per square kilometer (z-score relative to all cities) all_cities_z_daily_living Daily living score (z-score relative to all cities) all_cities_walkability Walkability index (sum of z-scores relative to all cities) first evaluated, in line with other studies that address road networks' representation with specific thresholds (Sehra et al, 2020). Second, a suitability analysis is conducted to evaluate the accessibility method (i.e., hexagon grid validation), which does not distinguish between hexagon neighborhoods that have one destination or ten destinations: in either scenario, there is access to at least one destination.…”
Section: Osm Destination and Edge Validationsupporting
confidence: 62%
“…One can query its database for street and intersection geometry data, along with attribute data about road types, names, and (when available) speeds, widths, and numbers of lanes (Jokar Arsanjani et al, 2015;Maier, 2014). It offers good global coverage and high geometric and topological data quality (Girres and Touya, 2010;Haklay, 2010;Corcoran et al, 2013;Zielstra et al, 2013;Barron et al, 2014;Basiri et al, 2016;Sehra et al, 2019). OpenStreetMap has more than 1 million contributors who have added over 6 billion nodes (points), 600 million ways (lines and boundaries), and attendant attribute data to its database.…”
Section: Global Street Network Datamentioning
confidence: 99%
“…One can query its database for street and intersection data, along with attribute data about road types, names, and (when available) speeds, widths, and numbers of lanes. It offers good global coverage and high geometric and topological data quality (Girres and Touya 2010; Haklay 2010; Corcoran, Mooney, and Bertolotto 2013; Zielstra, Hochmair, and Neis 2013; Barron, Neis, and Zipf 2014; Maier 2014; Basiri et al 2016; Sehra et al 2020). Barrington‐Leigh and Millard‐Ball (2017) found that, as of 2016, OpenStreetMap was 83% complete worldwide, over 40% of countries’ (including many developing countries) street networks were effectively 100% complete, and completeness was highest in both dense cities and sparsely populated areas.…”
Section: Introductionmentioning
confidence: 99%